Analisis ekonomi pajak bumi dan bangunan perdesaan dan perkotaan di Kabupaten Tanjung Jabung Barat - Periyanto Periyanto; Haryadi Haryadi; Nurhayani Nurhayani (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2017)
This study aims to analyze: (1) the development, contribution and effectiveness of Urban-Rural Land and Building Tax (PBB-P2) in Tanjung Jabung Barat District, (2) factors that influence PBB-P2 revenue. The data used are secondary data of Tanjung Jabung Barat District during the period 2004 - 2013. Data is sourced from the Central Statistics Agency and the Regional Revenue Service of Tanjung Jabung Barat Regency. The analysis tool uses descriptive statistics and multiple regression. The results of the study found: 1) based on its development, PBB-P2 is a very potential tax revenue in Tanjung Jabung Barat Regency, however, the contribution of PBB-P2 revenue to categorized PAD is very low. The effectiveness of PBB-P2 revenue is categorized as ineffective and tends to be not optimal in achieving the targets set 2) Simultaneously GDP per capita and the number of PBB-P2 taxpayers have a significant effect on PBB-P2 revenue, whereas only partially per capita GRDP has a significant effect